Trends in financial decision-making : planning and capital investment decisions - Dam, C. van (Leiden ; Boston : Nijhoff Social Sciences Division, 1978)
This books are intended for those who are interested for new developments in the decision-making area. They are especially suitable for graduate or advanced undergraduate courses: volume 1 in managerial or financial accounting courses; volume 2 in courses on managerial finance, capital budgeting or decision-making; and volume 3 in courses on business ethics or related fields.
Volume 2
Includes bibliographical references and index.
hza 06/07/2018
Loans
Keywords: Corporations; Capital investments; Decision making